A Multicenter, Cross-Sectional Study of the Incidence of Major Macular Diseases That Cause Visual Impairment and Require Therapeutic Intervention in Greece: The ADVICE Study - Karagiannis DA (Dove Medical Press, 2020)
Dimitrios A Karagiannis,1 Meropi Lygerou,2 Georgios Papadopoulos,3 Stamatina A Kabanarou,4 Miltiadis Aspiotis5,†, Doukas C Dardabounis,6 Panagiotis G Minakakis,7 Sofia I Spai,8 Chrysanthi Koutsandrea,9 Panagiotis Oikonomidis,10 Georgia N Pantelopoulou,11 Olga C Kousidou,11 Miltiadis Tsilimbaris12 On Behalf of the ADVICE study group1Ophthalmiatrio Athens Hospital, Athens 10672, Greece; 2OMMA, Ophthalmological Institute of Athens, Athens 11525, Greece; 3Ophthalmology Clinic, General Hospital of Aigio, Aigio, Greece; 4Retina Department, Korgialeneio Benakeio Hellenic Red Cross Hospital, Athens 11526, Greece; 5Ophthalmology Department, University of Ioannina, Ioannina 45500, Greece; 6Ophthalmology Clinic, University Hospital of Alexandroupolis, Dragana 68100, Alexandroupolis, Greece; 7Ophthalmological Clinic, General Hospital of Nikea-Piraeus, Nikea 18545, Greece; 8Ophthalmology Clinic, Sismanogleio General Hospital of Athens, Athens, Greece; 9National and Kapodistrian University of Athens, Filothei, Athens 15237, Greece; 10Ophthalmology Clinic, University General Hospital of Thessaloniki AHEPA, Thessaloniki, Greece; 11Novartis Hellas, Medical Department, Athens, Greece; 12Ophthalmological Clinic, University Hospital of Heraklion, Heraklion, GreeceCorrespondence: Olga C KousidouNovartis Hellas, Medical Department, 12th Klm National Road No. 1, Athens, GreeceEmail olga.kousidou@novartis.comPurpose: This multicenter, epidemiological, cross-sectional study aimed to estimate the annual cumulative incidence of major macular diseases that cause visual impairment and require therapeutic intervention in the routine care of Greece.Methods: The study was carried out between December 2012 and May 2015 in 20 ophthalmology clinics. Over a one-year recruitment period per study site, all treatment naïve adult patients newly diagnosed with wet age-related macular degeneration, visual impairment due to diabetic macular edema or macular edema secondary to retinal vein occlusion requiring therapeutic management and who had not been diagnosed or treated for the same disease in the past were enrolled after providing informed consent. Study data were collected during the single study visit.Results: A total of 1532 incident cases were enrolled. The estimated annual cumulative incidence of wet age-related macular degeneration, diabetic macular edema and macular edema secondary to retinal vein occlusion requiring therapeutic management was 0.82 [95% confidence interval (CI): 0.76, 0.88; n=723], 0.63 (95% CI: 0.58, 0.69; n=559), and 0.29 (95% CI: 0.25, 0.32; n=250) per 10,000 cases, respectively.Conclusion: The study provides estimates of the incidence of major macular diseases causing visual impairment and requiring treatment in outpatient hospital settings in Greece, indicating a considerable socioeconomic burden to the healthcare system.Keywords: anti-VEGF, diabetic macular edema, epidemiology, incidence, retinal vein occlusion, wet age-related macular degeneration